2020
DOI: 10.4103/jehp.jehp_491_20
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety among medical students: A comparison between preclinical and clinical years of training

Abstract: OBJECTIVE: It is common among medical students to falsely attribute bodily sensations/symptoms and holds a belief of having a medical illness with varying level of conviction. We studied and compared this condition known as “medical student syndrome”, a type of hypochondriasis, between preclinical and clinical years students. METHODOLOGY: This research was a descriptive study where a total of 100 students were approached and were asked to complete a short form of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…Consistent with previous findings, anxiety sensitivity was positively, significantly, and highly associated with hypochondria (Boysan et al, 2017 ; Fawaz & Samaha, 2021 ; Guo et al, 2020 ; Jhanwar et al, 2021 ; Starcevic et al, 2020a , b ). This finding suggests that being preoccupied with the irrational belief of over-focusing on somatic functions may be a risk factor for developing hypochondria and misinterpreting symptoms as a critical disease.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with previous findings, anxiety sensitivity was positively, significantly, and highly associated with hypochondria (Boysan et al, 2017 ; Fawaz & Samaha, 2021 ; Guo et al, 2020 ; Jhanwar et al, 2021 ; Starcevic et al, 2020a , b ). This finding suggests that being preoccupied with the irrational belief of over-focusing on somatic functions may be a risk factor for developing hypochondria and misinterpreting symptoms as a critical disease.…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta-analysis study showed that people who experience compulsive use of the Internet exhibit cyberchondria behaviors and increased health-related anxiety levels (McMullan, Berle, Arnaez, & Starcevic, 2019 ). A better understanding of the magnitude and direction of the correlations between students’ characteristics and growing hypochondria enables them to manage their anxieties (Jhanwar et al, 2021 ). Previous literature has studied each concept apart (Jokic-Begic et al, 2020 ; Hashemi et al, 2020 ; Selvi et al, 2018 ; Siste et al, 2021 ; Starcevic & Berle, 2013 ).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The results shows that the health science students had higher health anxiety compare to non-health science students. 11 In our study the heath related anxiety or hypochondrial attitude is higher among nursing students as compare to other department students. The finding is congruent with the previous studies wherein the medical students have higher hypochondrial attitude and health related anxiety as compare to other department students.…”
Section: Discussionmentioning
confidence: 47%